O sofrimento ético-político na vida intra e extra religiosa de filhos de Umbanda na cidade de São Paulo - Pereira, Jamila Casimiro (2012)
This work is based on the assumption that even though currently there is an incentive to the idea of human diversity and religious plurality, still there are manifestations against many of them. The object of this study is the objective and subjective settings in the process of maintaining religious belonging in the context of the everyday life demands of people affiliated to Umbanda in São Paulo. In order to know about this reality members of an Umbanda temple in the Barra Funda neighborhood of São Paulo were interviewed. This urban space was crucial to answer questions about the Umbanda community in the city, still operating in the field of studies of populations of African traditionalism in Brazil, regarding the history of black people in the neighborhood and in São Paulo city. The life histories of 4 adults identified as umbandistas and with a variety intra-religious and non-religious life trajectory were analyzed. The analysis of the interviews revealed four meaningful cores of the experience of being affiliated to Umbanda: the territory of encounter, the religious belonging, the maintenance of belonging, and the overcoming of resentment and inaction. The mediating analysis category of the life stories was the affection. It was chosen because it has been the motivational basis of the action of the subject and it condenses the subjective determinations of their social condition. The reference authors about affection are Espinosa, Vygotsky and Sawaia. The results of this study reveal that the umbandist subject, within everyday modernity, still lives situations of perverse inclusion, suffering with the ethical-political bias that surrounds this religion, which is objectified in the way of feeling and acting on reality itself. The historical aspects of Bantu African traditionalism that still remain in the dynamics of this religion it is a dimension of the Umbanda that favors life force, unlike other religions, because it does not alienate their practitioners in a transcendental power, inhibiting reflection and keeping them in the hope for miracles. Instead, extraordinary events occur in terms of its power to transform the ordinary life of these subjects, but the changes that are produced are not magical, they rely on rational thought and action of people in their set of subjective and objective conditions configured in good or bad encounters